2020
DOI: 10.1038/s41419-020-03135-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-182-5p and miR-378a-3p regulate ferroptosis in I/R-induced renal injury

Abstract: Renal tubular cell death is the key factor of the pathogenesis of ischemia/reperfusion (I/R) kidney injury. Ferroptosis is a type of regulated cell death (RCD) found in various diseases. However, the underlying molecular mechanisms related to ferroptosis in renal I/R injury remain unclear. In the present study, we investigated the regulatory role of microRNAs on ferroptosis in I/R-induced renal injury. We established the I/R-induced renal injury model in rats, and H/R induced HK-2 cells injury in vitro. CCK-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 57 publications
4
103
0
Order By: Relevance
“…Ding et al further con rmed that hypoxia-reoxygenation was able to promote the upregulation of miR-182-5p and miR-378a-3p in renal tubular epithelial cells in vitro, resulting in glutathione peroxidase 4 (GPX4) and SLC7A11 downregulation and consequent ferroptotic injury. Consistently, silencing these two miRNAs in an in vivo rat renal IR model system was su cient to suppress ferroptotic renal injury [10]. However, further work is required to fully elucidate the regulatory roles of individual miRNAs in the context of ferroptosis-induced renal IR injury.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Ding et al further con rmed that hypoxia-reoxygenation was able to promote the upregulation of miR-182-5p and miR-378a-3p in renal tubular epithelial cells in vitro, resulting in glutathione peroxidase 4 (GPX4) and SLC7A11 downregulation and consequent ferroptotic injury. Consistently, silencing these two miRNAs in an in vivo rat renal IR model system was su cient to suppress ferroptotic renal injury [10]. However, further work is required to fully elucidate the regulatory roles of individual miRNAs in the context of ferroptosis-induced renal IR injury.…”
Section: Introductionmentioning
confidence: 83%
“…miRNAs can serve as key regulators of gene expression [7], and both miRNA mimics and inhibitors have been highlighted as promising therapeutic tools in preclinical contexts [27]. Studies have shown that ischemia-reperfusion conditions result in the upregulation of miR-182-5p and miR-378a-3p, activating ferroptotic renal injury by downregulating GPX4 and SLC7A11 [10]. However, there have been relatively few prior analyses of how miRNAs modulate ferroptotic injury in the context of renal IR, and there have been no reports regarding miRNA-mediated HMOX1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…we identified that miR-182 could target the seeding region spanning rs3743104 at the 3′-UTR of GREM1 , which suppresses the transcription of GREM1 . miR-182 has been reported as a biomarker for kidney injury and bladder cancer, and a regulatory miRNA binding to 3′-UTR of gene targets to the progression of diseases [ 32 , 33 ]. It's worthy of further work that how miR-182 is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrostatin-1 Inhibit lipid peroxidation myocardial, cerebral, and liver I/R injury Tuo et al, 2017;Fang et al, 2019;Yamada et al, 2020 Dexrazoxane Chelation of iron myocardial I/R injury Fang et al, 2019 Deferoxamine Reduce intracellular iron myocardial, cerebral, liver, and testicular I/R injury Hanson et al, 2009;Li et al, 2018;Yamada et al, 2020;Tu et al, 2021 Liproxstatin-1 Inhibit lipid peroxidation myocardial, cerebral, liver, intestinal, pulmonary, and testicular I/R injury Friedmann Angeli et al, 2014;Tuo et al, 2017;Li et al, 2018;Feng et al, 2019;Li Y. et al, 2019;Xu et al, 2020 MicroRNAs (miRNAs) are a class of small non-coding RNAs that function in various biological processes involving cell death. In I/R-induced renal injury, miR-182-5p and miR-378-3p are upregulated, which promotes the activation of ferroptosis through the downregulation of GPX4 and SLC7A11 (Ding et al, 2020), indicating that ferroptosis may be regulated by multiple I/R-related miRNAs and targeting these miRNAs could provide novel therapeutic methods to suppress ferroptosis and I/R injury.…”
Section: Mechanism Diseases Referencesmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small non-coding RNAs that function in various biological processes involving cell death. In I/R-induced renal injury, miR-182-5p and miR-378-3p are upregulated, which promotes the activation of ferroptosis through the downregulation of GPX4 and SLC7A11 ( Ding et al, 2020 ), indicating that ferroptosis may be regulated by multiple I/R-related miRNAs and targeting these miRNAs could provide novel therapeutic methods to suppress ferroptosis and I/R injury.…”
Section: Ferroptosis and I/r Injurymentioning
confidence: 99%